THE INFLUENCE OF HUMAN RESOURCE QUALITY, ORGANIZATIONAL CLIMATE, AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE - Yanti , Noor; Agustina, Titien; Jaya, Fanlia Prima (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the influence of human resource quality, organizational climate, and organizational commitment on employee performance at the Health Training Center (Balatkes) in South Kalimantan Province. This research is a quantitative study. The population and sample size were 47 people. Data collection used a questionnaire with a Likert scale. Analysis used multiple linear regression.The results of the study indicate that simultaneously, human resource quality, organizational climate, and organizational commitment significantly influence the performance of Bapelkes employees in South Kalimantan Province. Meanwhile, partially, human resource quality does not significantly influence the performance of Bapelkes employees in South Kalimantan Province. However, organizational climate and organizational commitment each partially show an influence on the performance of Bapelkes employees in South Kalimantan Province. Keywords: Human Resource Quality, Organizational Climate, Organizational Commitment, Employee Performance